Evaluation of sustainable development of the Bohai Sea Rim based on integrated land–sea management: a multi-system coupling and coordination study at coastal, provincial, and city level - Yan, Jinling; Xue, Yongjie; Wu, Huilan; Li, Dahai; Mohsin, Muhammad (Frontiers in Marine Science, 2023)
Based on the Integrated Land–Sea Management, this study established a theoretical framework for the sustainability of coastal regions by combining sustainable development with coupling coordination theory. The improved coupling coordination model was used to analyze the sustainable development of the Bohai Rim and its coastal provinces and cities from 2006 to 2020. Our implications were as follows: (1) The theoretical framework showed an S-shaped spiral trend, and the empirical results on the Bohai Rim were consistent with the trajectory conclusions. (2) The economic subsystem played a crucial role in the system’s evolution toward sustainable development. (3) The region and city models demonstrated consistent coupling and coordination development degrees. However, the consistency was not completely synchronous. Conscious eco-environmental governance activities can promote benign interactions among systems and improve this relationship. (4) The sustainable development of coastal cities is different from that of the provinces in which they are located. It merely demonstrates their relative status among all coastal cities and does not fully represent the wider region in which they are located. The findings suggest that adaptive policies, whether economic, social or environmental, can promote sustainable development. Economic stimulus policies can promote a transition of sustainable development; in the economic downturn, the adaptive environmental policy is realized by adjusting the relationship between subsystems to promote the coordination of regional systems, preparing for the next sustainable system transition. The established theoretical model and improvised mathematical method can be extended to study various coastal regions